If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 4 = 10x + -6 Reorder the terms: 4 + 3x = 10x + -6 Reorder the terms: 4 + 3x = -6 + 10x Solving 4 + 3x = -6 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 4 + 3x + -10x = -6 + 10x + -10x Combine like terms: 3x + -10x = -7x 4 + -7x = -6 + 10x + -10x Combine like terms: 10x + -10x = 0 4 + -7x = -6 + 0 4 + -7x = -6 Add '-4' to each side of the equation. 4 + -4 + -7x = -6 + -4 Combine like terms: 4 + -4 = 0 0 + -7x = -6 + -4 -7x = -6 + -4 Combine like terms: -6 + -4 = -10 -7x = -10 Divide each side by '-7'. x = 1.428571429 Simplifying x = 1.428571429
| 18/x-4=10/x | | X/7+1=-1 | | 1/3x+y=6 | | X-a+4=ax+2b-6 | | 1/2(4a+10)=2+ | | 9=5x-4x+5 | | 4ab+9=c | | -1.5(a+1)=0.5(a-9) | | -1.5(a+1)=0.5(a-9) | | 2/3*8=51/3 | | Y=2(-1/3)+7 | | v-2/2=4/3 | | -3.2=[8p] | | -4a/9-6=4 | | -3(16+3)+4(24+1)=43 | | 1/3t-4/3=-5/4t-3/2 | | 12/5=4w | | 2/3*8 | | 2(a+4)/2=14 | | 3x-27=14 | | 4.5=5t | | -2/7u+5/4=-3/8u+1/4 | | 0.5x+3=0.12x-2 | | 15.4r=61.6 | | 6(v+3)=72 | | 2z+9z=4z+45+2r | | -4x-8x=0 | | 4(-1/3)=x | | -3[d-5]=-6 | | (4+56/8x3)/5 | | -6r+4r=-14 | | 3b-q=14+2b |